Analysis Of The Vrijspraak Decision Of The Bireuen District Court Number : 202/Pid.Sus/2024/Pn Bir And Examination Of The Public Prosecutor's Cassation Decision Number: 7506 K/Pid.Sus/2025: - - Putra, Muhammad Iqbal Mannur; Ariadi, Agus (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze in depth the dynamics of criminal procedural law in narcotics cases through a case study of the Bireuen District Court's Vrijspraak Decision Number : 202/Pid.Sus/2024/PN Bir and an examination of the Cassation decision submitted by the Public Prosecutor, namely the Supreme Court Decision Number : 7506 K/Pid.Sus/2025. This study uses a normative legal research method, which analyzes court decisions as positive rules. The case approach is used to critically compare the ratio decidendi of two court decisions at different levels. The results of the study indicate that the Bireuen District Court erred in applying the doctrine of limited negative evidence by prioritizing the lack of physical control of narcotics (insufficient valid evidence), which resulted in the failure to form a conviction in the judge. The Public Prosecutor challenged the decision by arguing an error in the application of the law (onjuiste toepassing van het recht). The Supreme Court, as judex juris, corrected the error in the ruling by confirming that the element of